The meaning of Jewish culture of origin for Jewish women from the third generation - Agnieszka Krawczyk (Kultura i Wychowanie, 2024)
This article draws on four free-form interviews with elements of narration, which I conducted with representatives of the “third generation” of people of Jewish origin living in Łódź. In my text, I refer to the knowledge (and lack of knowledge) of the surveyed women as to their roots. I also distinguish two family models they have created. I place Jewish culture and religion in the context of the women’s everyday experiences.